Small intestine-derived gastrointestinal stromal tumour diagnosed synchronously with colon adenocarcinoma: a case report and review of the literature - Tanriverdi, Ozgur; Meydan, Nezih; Barutca, Sabri; Sargin, Gokhan; Tataroglu, Canten; Meteoglu, Ibrahim (Contemporary Oncology/Współczesna Onkologia, 2011)
Gastrointestinal stromal tumours (GISTs) account for 0.1-3% of all gastrointestinal cancers. Although nausea, emesis, abdominal pain, GIS haemorrhage, and non-specific symptoms associated with metastatic disease are common, asymptomatic cases are not rare. They are located in the stomach in approximately 60-70% of cases, and in the small intestine in 20-30% of cases. Gastrointestinal stromal tumours can be seen synchronously or metachronously with other epithelial cancers. The co-occurrence of colon adenocarcinomas and GISTs in the small intestine is not common. The genetic pathways in the tumourigenesis of two different neoplasms (GIST and colorectal adenocarcinoma) being different was suggested as a probable cause; however; although the number of cases is limited, some researchers have reported that they could not rule out the possibility that this association is not coincidental. Herein we present a patient who was concomitantly diagnosed with a GIST as a result of an ileal lesion biopsy performed during surgery for colon adenocarcinoma.